Repeated Negative Teaching Evaluations: A Form of Habitual Behaviour? - Grayson, J Paul (Canadian Journal of Higher Education, 2015)
Teaching evaluations have become part of life on Canadian campuses; however, there is no agreement among researchers as to their validity. In this article, comparisons were made between first- and third-year collective evaluations of professors’ performance at the University of British Columbia, York University, and McGill University. Overall, it was found that students who provided low evaluations in their first year were also likely to do so in their third year. This effect held independent of degree of campus engagement, sex, student status (domestic or international), and generational status (students who were the first in their families to attend university, compared to those who were not). Given that over the course of their studies, students likely would have been exposed to a range of different behaviours on the part of their professors, it is argued that the propensity of a large number of students to give consistently low evaluations was a form of “habitual behaviour.”